2014
DOI: 10.1097/rhu.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Bowel-Associated Dermatosis-Arthritis Syndrome in an Adolescent With Short Bowel Syndrome

Abstract: Bowel-associated dermatosis-arthritis syndrome (BADAS) is a neutrophilic dermatosis, characterized by the occurrence of arthritis and skin lesions related to bowel disease with or without bowel bypass. We report an unusual case of BADAS in a 15-year-old white male with congenital aganglionosis of the colon and hypoganglionosis of the small intestine and multiple bowel surgeries in childhood complicated by short bowel syndrome. He presented with recurrent peripheral polyarthritis, tenosynovitis, and painful ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Currently, little is known about the pathogenesis of BADAS. It has been suggested that intestinal inflammation and bacterial overgrowth may lead to abnormal activation of the immune system, which in turn leads to the deposition of immune complexes on the skin and synovium [ 3 ]. The histological appearance of BADAS is not characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, little is known about the pathogenesis of BADAS. It has been suggested that intestinal inflammation and bacterial overgrowth may lead to abnormal activation of the immune system, which in turn leads to the deposition of immune complexes on the skin and synovium [ 3 ]. The histological appearance of BADAS is not characteristic.…”
Section: Discussionmentioning
confidence: 99%
“… 2 BADAS has also been reported as the presenting prodrome of Crohn's disease in an adolescent, however to our knowledge, this case illustrates one of the youngest pediatric patients with this condition in the English-language literature. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates ( n = 232) and articles deemed not relevant through title and abstract screening ( n = 328), 56 articles were evaluated in full text. Among them, 51 articles (comprising 42 individual case reports and 9 case series) fulfilled the eligibility criteria [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ,…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: All included publications presenting cases of patients with bowel-associated dermatosis-arthritis syndrome; Table S2: Cases excluded. References [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ,…”
mentioning
confidence: 99%